Analisis Kesulitan Guru Dalam Pembelajaran Daring pada Masa Pandemi Covid-19 di SD Negeri 21 Palembang - Prasetya, Yola; Ferdiansyah, M; Prasrihamni, Mega (Indonesian Research Journal on Education, 2022)
The purpose of this study is to find out the difficulties of teachers in online learning during the Covid-19 pandemic in SD Negeri 21 Palembang. The methods used in this study are qualitative descriptive. Methods that use by collecting sources systematically and using data sources in depth. Qualitative descriptive research is outlined with words according to respondents, what is in accordance with the research question, then analyzed with what words are behind the respondent in behaving (thinking, callous, and acting). The subject in research use the Teacher on 1,2,3,4,5,and 6 class SD Negeri 21 Palembang. The data analysis techniques used in this study are data reduction, data presentation and conclusions. The results showed that the difficulty of teachers during online learning is to make RPPthat is in accordance with online learning steps, create learning media for the online learning process, prepare materials or teaching materials for the online learning process, learning methods used by teachers for the online learning process, assess student characteristics for the online learning process, readiness of students for the online learning process, use the facilities and infrastructure for the online learning process, approach the online learning process, and evaluate the results of the online learningprocess. The conclusion of this study is that the difficulty of teachers during online learning in SDNegeri 21 Palembang there are many obstacles, the majority of teachers say that during this onlinelearning process can not run effectively and maximally because of distance limitations.